2008
DOI: 10.1161/circulationaha.108.787598
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Predictors of Fetal Aortic Coarctation

Abstract: Background-Prenatal diagnosis of aortic coarctation suffers from high false-negative rates at screening and poor specificity. Methods and Results-This retrospective study tested the applicability of published aortic arch and ductal Z scores (measured just before the descending aorta in the 3-vessel and tracheal view) and their ratio on 200 consecutive normal controls at a median of 22Ϯ0 gestational weeks (range, 15Ϯ4 to 38Ϯ4 weeks). Second, this study tested the ability of serial Z scores to distinguish fetuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
148
5
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(183 citation statements)
references
References 19 publications
15
148
5
15
Order By: Relevance
“…The ultrasonographic diagnosis includes also Z-scores of the ascending aorta and aortic isthmus dimensions. Isthmal to ductal ratio may be helpful in exclusion of the CoA too 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasonographic diagnosis includes also Z-scores of the ascending aorta and aortic isthmus dimensions. Isthmal to ductal ratio may be helpful in exclusion of the CoA too 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Arch obstruction occurs in the fetus; it is not a postnatal event but a dynamic situation in the fetus [9]. Diagnostic accuracy may be improved by means of combining size-based cardiac parameters with gestational age at diagnosis [10].…”
Section: Prenatal Predictionmentioning
confidence: 99%
“…This leads to increased morbidity and mortality in affected neonates without correct prenatal diagnosis, who often collapse and require resuscitation before surgery [2,4,5] and unjustified costs of cardiac centers due to false-positive cases [6]. Despite advances in fetal echocardiography and the description of antenatal findings associated with neonatal CoAo, this lesion remains the most challenging diagnosis to be made in fetal and early neonatal life [6][7][8][9][10].To the best of our knowledge quantitative fetal Doppler criteria of neonatal CoAo have not been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unique parallel circulation of the fetus with right and left ventricles that have comparable filling pressures and afterload, the presence of fetal shunts, and the lack of clinical information beyond noninvasive imaging provides unique challenges to defining lesion severity. For instance, retrograde ductus arteriosus flow in lesions with pulmonary stenosis heralds critical obstruction [14]; however, in its absence, the severity of pulmonary outflow obstruction is often grossly inferred by the size and growth of the main pulmonary artery and its size relative to the aorta [15,16].in ventricular, great artery and, most consistently, arch size may be the only abnormalities identified that lead to a suspected diagnosis of discrete juxtaductal coarctation of the aorta which clinically manifests postnatally only after the ductus arteriosus begins to constrict ( Figure 2) [17,18]. Occasionally in more severe coarctation, however, distal arch hypoplasia and a posterior shelf may be identified, but even then, determining whether the lesion will warrant neonatal surgical intervention may not be possible until after ductal constriction in the neonatal period [19].…”
Section: Structural Heart Disease In the Fetusmentioning
confidence: 99%